Learning OpenCV 4 computer vision with Python 3 get to grips with tools, techniques, and algorithms for computer vision and machine learning - Howse, Joseph, 1984- (Packt Publishing, 2020)
Now in its third edition, this is the original book on OpenCV's Python bindings. Readers will learn a great range of techniques and algorithms, from the classics to the state-of-the-art, and from geometry to machine learning. All of this is in aid of solving practical computer vision problems in well-built applications.